The art of nature conservation - Radley, Donna (2020)
This original research makes a first attempt to understand some of the origins of the visual culture of UK nature conservation, and how it has developed over the last seventy years or so. The history and communication work of the statutory nature conservation agencies are described using evidence provided through interviews with former and current staff members and analysis of published material. Interviews with wildlife artists and surveys of two specific groups of the public have revealed further information about imagery conveying nature conservation messages.